The Influence of Digital Fatigue and Occupational Stress on Quiet Quitting in Generation Y and Z in the Agency Industry - Kartika, Leni Ajeng; Gularso, Kurnadi; Pangaribuan, Christian Haposan (Jurnal Multidisiplin Indonesia, 2025)
This research investigates the influence of digital fatigue on quiet quitting among Generation Y and Z employees in the agency industry, with occupational stress as a mediating variable. The study sampled 236 respondents from various divisions predominantly under contract employment and using digital technology intensively (10-12 hours daily). Validity and reliability tests confirmed the soundness of the measurement instruments. Structural Equation Modeling (SEM) analysis showed that digital fatigue significantly increases occupational stress and quiet quitting behaviors. Occupational stress also partially mediates the relationship between digital fatigue and quiet quitting. These findings highlight the critical impact of digital workloads on employee engagement and underline the need for managerial strategies to mitigate digital fatigue and occupational stress to enhance work productivity and reduce quiet quitting. The study contributes to practical solutions for managing employee well-being in highly digital and demanding agency work environments.